2016
DOI: 10.1016/bs.adomc.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Lithium, Sodium, and Potassium Magnesiate Chemistry

Abstract: Until recently, deprotonative metalation reactions have been performed using organometallic compounds that contain only a single metal (e.g., organolithium reagents). Since the turn of the millennium, bimetallic compounds such as alkali metal magnesiates have begun to emerge as a new class of complementary metalating reagents. These have many benefits over traditional lithium compounds, including their enhanced stability at ambient temperatures, their tolerance of reactive functional groups and their stability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Organomagnesium compounds have been known for more than a century, and in 1912, Victor Grignard was awarded with the Nobel Prize for the achievement of introducing organomagnesium halides, the so-called Grignard reagents, to organic and organometallic chemistry [7]. Still today, the coordination and organic chemistry of magnesium offers many facets for future tasks [8][9][10][11]. A few years after the discovery of the Grignard reagents, organolithium chemistry was developed by the research groups of Gilman [12] and Schlenk [13] and long lasting, extensive research efforts now allow us to understand the chemistry of these light s-block metals [14].…”
Section: Toxicity Of Elementmentioning
confidence: 99%
“…Organomagnesium compounds have been known for more than a century, and in 1912, Victor Grignard was awarded with the Nobel Prize for the achievement of introducing organomagnesium halides, the so-called Grignard reagents, to organic and organometallic chemistry [7]. Still today, the coordination and organic chemistry of magnesium offers many facets for future tasks [8][9][10][11]. A few years after the discovery of the Grignard reagents, organolithium chemistry was developed by the research groups of Gilman [12] and Schlenk [13] and long lasting, extensive research efforts now allow us to understand the chemistry of these light s-block metals [14].…”
Section: Toxicity Of Elementmentioning
confidence: 99%
“…of L-LA in 90 or 110 °C in 24 or 36 h, respectively. 30,31 Another example was the magnesium-lithium 1,3-dipropoxy-p-tertbutylcalix [4]arene complex, which converted (9%) 100 equiv. of rac-LA in the presence of 1 equiv.…”
Section: Introductionmentioning
confidence: 99%
“…Synergic behavior arising from the chemical cooperativity of two different metal species allows transformations to be per-formed that would be unachievable using conventional monometallic reagents. Most reported systems are based on alkyl/ aryl, 4,5 or amido 6 alkali metal magnesiates, which were applicable for magnesium-halogen exchange of aryl substrates, 7 enantioselective alkylation of aldehydes, 8 cyclization of alkynols, 9 transfer hydrogenation of alkenes, 10 or hydroamination of alkynes and alkenes. 11 In organic synthesis, very important synergistic heterobimetallic reagents were alkyl or amido alkali metal-magnesium halides, so-called turbo-Grignard or turbo-Hauser bases.…”
Section: Introductionmentioning
confidence: 99%
“…the spectra are highly symmetric, indicating that any close M•••C-H contacts observed in the solid state (see below) are not maintained in d 6 -benzene solutions at 298 K, and there is no evidence of complex aggregation. Minor impurities seen in the 1 H and 13 C{ 1 H} NMR spectra of 2-4 may be attributed to the formation of alkali metal magnesiates 32. This intriguing possibility could be verified by the rational synthesis of such complexes; whilst this is beyond the scope of this study we note that {N(Si t BuMe 2 ) 2 } has previously been shown to capable of bridging between K + and Ln 2+ (Ln = Sm, Eu, Tm, Yb) cations.24f We examined complexes 2-4 and 6 by 1 H DOSY NMR spectroscopy in d 8toluene to determine if these minor impurities could be assigned to higher-order aggregates.…”
mentioning
confidence: 99%